2016
DOI: 10.1080/01634372.2016.1268231
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Care Perceptions of Older Women and Middle Adolescents in a Resource-Constrained Community in South Africa

Abstract: This study describes intergenerational care perceptions in a resource-challenged community. Ten women (aged 60+) and eight middle adolescents (3 boys and 5 girls) participated in the Mmogo-method®, a visual data-collection method. Textual data were analysed thematically, and visual data by applying Roos and Redelinghuys (2016) proposed steps. Both groups provided physical and instrumental care to the other. Older women cared for adolescents by teaching and disciplining them, while the adolescents cared for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Older persons perceived younger people as stubborn, disobedient, and disrespectful, while younger people experienced older people as rigid, demanding, and sometimes abusive (Chigeza et al, 2021). Intergenerational interactions around mobile phone and generational expectations of giving and receiving care confirmed unsatisfactory generational experiences and perceptions (Roos & Robertson, 2019;Roos, et al, 2017). Yet it was unclear what actually occurred to activate social power and explain what deeper social structures were involved in the relational dynamics between older persons and younger people, particularly in a traditional, rural community.…”
Section: Example Of the Mmogo-methods In Applying Cidamentioning
confidence: 94%
“…Older persons perceived younger people as stubborn, disobedient, and disrespectful, while younger people experienced older people as rigid, demanding, and sometimes abusive (Chigeza et al, 2021). Intergenerational interactions around mobile phone and generational expectations of giving and receiving care confirmed unsatisfactory generational experiences and perceptions (Roos & Robertson, 2019;Roos, et al, 2017). Yet it was unclear what actually occurred to activate social power and explain what deeper social structures were involved in the relational dynamics between older persons and younger people, particularly in a traditional, rural community.…”
Section: Example Of the Mmogo-methods In Applying Cidamentioning
confidence: 94%
“…Research on intergenerational relational experiences in rural South Africa are reportedly strained: older people are dissatisfied with younger people's caring for and about them, and treating them disrespectfully (Aboderin & Hoffman, 2015;Roos, 2016;Roos, Silvestre, & De Jager, 2017), while younger people expressed negative perceptions in anticipation of unpleasant relational interactions, frustrating contact, and a breakdown of relations with older people (Roos & Robertson, 2019). The impact of ineffective intergenerational contact is particularly profound in this and other rural settings in South Africa because it contributes to older people's vulnerability, compromised reciprocal care for generational members, and relational wellbeing in general (Roos et al, 2017).…”
Section: Interpersonal Contextmentioning
confidence: 99%
“…Relational qualities are observable behavior, consisting of actions and reactions between interacting people, which manifest on a continuum from effective to ineffective (see Roos, 2016Roos, , 2018Roos & Du Toit, 2014;Vorster et al, 2013). In this particular context, research indicated that ineffective relational qualities, such as judgment (lack of empathy), conditional acceptance, and lack of perspective-taking are likely to elicit rejection from a participating person, or escalating, sometimes ineffective, attempts to address their psychological needs or social goals (Roos et al, 2017;Roos & Wheeler, 2016).…”
Section: Interpersonal Contextmentioning
confidence: 99%
“…They either visit each other by walking down the hall or driveway; or, both generations come to a common space to interact and engage with each other. Examples of these modes include the TreeHut School (United States) (Murphy 1984), PACE Maluhia (Hawaii) (Larson, 2000), Valspan community (South Africa) (Roos, Silvestre & De Jager, 2017) Stride Rite Stride Rite (United States) (Laabs, 1993) and Intergenerational Summer Program (United States) (Giglitotti et al, 2005) and ONEGeneration (United States) (Jarrott & Bruno, 2007). In the TreeHut School, PACE Maluhia and Valspan community elderly participants live at a retirement village or in a residential aged care centre, and the children attend a formal day care program.…”
Section: What Is An Intergenerational Care Program?mentioning
confidence: 99%